Machinery structure, machinery subsidies, and agricultural productivity: Evidence from China - Meng Meng; Leng Yu; Xiaohua Yu (Agricultural Economics, 2024)
Although agricultural machinery is indispensable for modern agriculture, the effect of machinery structure on food production is rarely scrutinized. Machinery structure, referring to the proportion of high-capacity machines which are represented by tractors with relatively high horsepower, is used to measure the scale of agricultural machinery. In response, this article investigates how agricultural machinery structurally impacts grain production theoretically and empirically, with particular emphasis on the effects of capacity structure and subsidy policy. The article estimates a Translog production function with a panel dataset covering 126 counties across Xinjiang and Hubei provinces in China from 2002 to 2012. Though we find the general elasticity of output with respect to machinery inputs is .03, the capacity structure of agricultural machines could impact agricultural production by inducing the reallocation of other input factors. Along with the upsizing of farming machines, we observe the complementarity between machinery horsepower and land inputs in production increases, while the joint effect of machinery and fertilizer decreases. The positive land channel is found in areas with fewer high-capacity machines, while the negative fertilizer channel occurs when there are more large machines.
Keywords: 330; agricultural mechanization; agricultural subsidy; capacity structure effect; food security; grain production